PROVISIONAL STENTING IN LEFT MAIN STEM DISEASE: LONG-TERM OUTCOMES AND IMPACT ON SIDE BRANCH PERFUSION - KHATTAK , SN; RAJA, F; WALEED , M; KHAN , A (Biological and Clinical Sciences Research Journal, 2024)
Left main stem disease (LMSD) is a severe form of coronary artery disease (CAD) that involves a significant risk of mortality if not treated effectively. Traditionally, coronary artery bypass grafting (CABG) has been the primary method for revascularization in LMSD. However, percutaneous coronary intervention (PCI), especially provisional stenting using drug-eluting stents (DES), has gained popularity for its minimal invasiveness and comparable clinical outcomes. Provisional stenting allows treatment of the main vessel with additional side branch stenting only when needed, reducing complications and stent usage. Objective: The primary objective of this study is to evaluate the long-term outcomes of provisional stenting in patients with LMSD, focusing on its impact on side branch perfusion, in-stent restenosis (ISR), and major adverse cardiac events (MACE). Methods: This retrospective cohort study was conducted at a tertiary care hospital specializing in cardiology between January 2023 and December 2023. A total of 284 patients who underwent provisional stenting for LMSD were included. Fractional flow reserve (FFR) and quantitative coronary angiography (QCA) were used to assess side branch perfusion, with follow-up data including clinical outcomes such as ISR, MACE, and survival rates. Multivariate regression analysis was used to identify predictors of poor outcomes, and Kaplan-Meier survival curves were generated to compare outcomes based on side branch perfusion status. Results: The study found that 77.5% of patients achieved adequate side branch perfusion (FFR > 0.80) after provisional stenting, while 22.5% had impaired perfusion (FFR ≤ 0.80). The incidence of MACE was 10.6%, and ISR was reported in 7.0% of patients during the one-year follow-up period. Kaplan-Meier analysis showed a significant survival benefit for patients with adequate side branch perfusion (Log-Rank p < 0.001). Age and diabetes mellitus were significant predictors of MACE. Conclusion: Provisional stenting in LMSD provides favourable long-term outcomes, particularly in terms of side branch perfusion and reduced MACE. However, a subset of patients, particularly those with diabetes, may require additional interventions. Future studies should focus on improving outcomes in patients with impaired side branch perfusion and exploring the role of advanced imaging techniques in optimizing stenting strategies.